Are there theoretical ethics for today? - Bolo Romero, Karla Mavel (2017)
This paper analyzes three contemporary ethical postures, namely, Franz Hinkelammert’s critical ethics, Henry Dussel’s the ethics of liberation, and the ethics of communitarianism of Alasdair MacIntyre, in order to determine whether these ethical proposals make sense on a daily basis:. In order to do this, it first contextualized the Peruvian reality and the capitalism inserted within. Then, it critically analyzes the three ethical postures mentioned above. Finally, it examines whether these ethics may be redirected to solve real-life problems, not just theoretical ones.